An evaluation of kerogen molecular structures during artificial maturation. (1st April 2020) - Liang, Tian; Zou, Yan-Rong; Zhan, Zhao-Wen; Lin, Xiao-Hui; Shi, Jun; Peng, Ping'an
Highlights: ∑Iar was calculated to estimate aromatic clusters increment of kerogen. Condensation index was proposed to show the aromatic cluster increment of kerogen. Differences between multiple maturity ranges of structure were explored. Six kerogen molecular structures with maturity were established. Abstract: 13 C solid-state NMR and XPS techniques were used to investigate structural changes in kerogen during oil generation process across a range of maturity. Kerogen was isolated from an shale rock collected from Well W161 in the Dongying Depression, Bohai, China. An artificial pyrolysis experiment was carried out in a closed gold tube system using a heating rate of 2 ℃/h during which 11 temperature-point samples were collected between 350 ℃ and 450 ℃ (Easy%Ro = 0.80 to 1.98). The initial kerogen was analysed using Rock-Eval and the samples were analysed using X-ray photoelectron spectroscopy (XPS) and solid-state 13 C nuclear magnetic resonance ( 13 C NMR) to study their functional groups and chemical structures. Six averaged molecular structure models of the initial kerogen and its residues (can not be dissolved by organic reagent) were established to study the changes occurring during oil and gas generation. The results showed that with an increase in temperature, the proportion of aliphatic carbon declined while aromatic carbon increased. After reaching peak oil maturity, a condensation reaction occurred in the residue; some aromatic carbons cracked from the kerogen and combined with the residue structure. Average aromatic cluster increment was calculated to quantify the increase in the size of aromatic clusters within the structures. It was established to evaluate the changes occurring in the molecular structure of type Ⅰ kerogen during heating. Based on these results, ConU (maximum condensation degree) and ConL (lowest condensation degree) are proposed to estimate the degree of condensation of samples with different maturities.